Ahlussunnah Wal Jama'ah Communication Forum is an Islamic Political Organizational Movement in Legal Studies - Nugraha, Ridhoni Mirza; Sandhubaya, Gilang (Jurnal Cakrawala Hukum, 2023)
Indonesia's democratic transition post-reformation has changed the pattern of Indonesian politics. There were fluctuations and dynamics of Islamic political power during the New Order era. At the beginning of the New Order, Islam was marginalized from the state. Meanwhile, Islam encountered difficulties developing socio-political ideas because of the repressive New Order regime. It is interesting to note that although the majority of Indonesia's population is Muslim, nationalist political parties dominate every election. This article discusses complex unifying issues causing political turmoil: religion and the state. Much of Indonesia's current research on political Islam focuses on the rise of Islam-based political parties in domestic politics and the significant role of long-standing Islamic organizations such as Nahdlatul Ulama (NU) and Muhammadiyah. This topic is interesting to discuss because it is relatively new, discussing the fundamental issue, in this case, the problem of different understandings of the relationship between religion and the state. The research method used in this study is library research. Data obtained from literature research is used to understand the background, history, goals, and vision of FKAWJ and the political context of Islam in Indonesia. How to cite item: Nugraha, Ridhoni Mirza, and Gilang Sandhubaya. â€œAhlussunnah Wal Jama'ah Communication Forum is an Islamic Political Organizational Movement in Legal Studies.â€ Jurnal Cakrawala Hukum 14 no. 2 (2023): 212-222. DOI: doi.org/10.26905/idjch.v14i2.10174.